CKS1B as Drug Resistance-Inducing Gene—A Potential Target to Improve Cancer Therapy - Shi, Wenwen; Huang, Qiudi; Xie, Jiacui; Wang, He; Yu, Xiyong; Zhou, Yi (Frontiers in Oncology, 2020)
Abstract: Cancer is a threat to human health and life. Although previously centered on chemical drug treatments, cancer treatment has entered an era of precision targeted therapy. Targeted therapy entails precise guidance, allowing the selective killing of cancer cells and thereby reducing damage to healthy tissues. Therefore, the need to explore potential targets for tumor treatment is vital. Cyclin-dependent kinase regulatory subunit 1B (CKS1B), a member of the conserved cyclin kinase subunit 1 (CKS1) protein family, plays an essential role in cell cycling. A large number of studies have shown that CKS1B is associated with the pathogenesis of many human cancers and closely related to drug resistance. Here, we describe the current understanding of the cellular functions of CKS1B and its underlying mechanisms, summarize a recent study of CKS1B as a target for cancer treatment and discuss the potential of CKS1B as a therapeutic target.